Benefit of Bovine Viral Diarrhoea (BVD) Eradication in Cattle on Pestivirus Seroprevalence in Sheep - Huser, Andrea Franziska; Schär, Jessica Grace; Bachofen, Claudia; de Martin, Elena; Portmann, Jasmine; Stalder, Hanspeter; Schweizer, Matthias (Frontiers in Veterinary Science, 2021)
Bovine viral diarrhea virus (BVDV) and Border disease virus (BDV) are closely related pestiviruses of cattle and sheep, respectively. Both viruses may be transmitted between either species, but control programs are restricted to BVDV in cattle. In 2008, a program to eradicate bovine viral diarrhea (BVD) in cattle was started in Switzerland. As vaccination is prohibited, the cattle population is now widely naïve to pestivirus infections. In a recent study, we determined that nearly 10% of cattle are positive for antibodies to BDV. Here, we show that despite this regular transmission of BDV from small ruminants to cattle, we could only identify 25 cattle that were persistently infected with BDV during the last 12 years of the eradication program. In addition, by determining the BVDV and BDV seroprevalence in sheep in Central Switzerland before and after the start of the eradication, we provide evidence that BVDV is transmitted from cattle to sheep, and that the BVDV seroprevalence in sheep significantly decreased after its eradication in cattle. While BDV remains endemic in sheep, the population thus profited at least partially from BVDV eradication in cattle, which largely abolished spillover from cattle to sheep. Importantly, on a national level, BVDV eradication does not appear to be generally derailed by the presence of pestiviruses in sheep. However, with every single virus-positive cow, it is necessary to consider small ruminants as a potential source of infection, resulting in costly but essential investigations in the final stages of the eradication program.